Late-Onset Non-HLH Presentations of Growth Arrest, Inflammatory Arachnoiditis, and Severe Infectious Mononucleosis, in Siblings with Hypomorphic Defects in UNC13D - Gray, Paul Edgar; Shadur, Bella; Russell, Susan; Mitchell, Richard; Buckley, Michael; Gallagher, Kerri; Andrews, Ian; Thia, Kevin; Trapani, Joseph A.; Kirk, Edwin Philip; Voskoboinik, Ilia (Frontiers in Immunology, 2017)
Bi-allelic null mutations affecting UNC13D, STXBP2 or STX11 result in defects of lymphocyte cytotoxic degranulation, and commonly cause familial haemophagocytic lymphohistiocytosis (FHL) in early life. Patients with partial loss of function are increasingly being diagnosed after presenting with alternative features of this disease, or with HLH later in life. Here, we studied two sisters with lymphocyte degranulation defects secondary to compound heterozygote missense variants in UNC13D. The older sibling presented aged 11 with linear growth arrest and delayed puberty, two years prior to developing transient ischaemic attacks secondary to neuroinflammation and hypogammaglobulinaemia, but no FHL symptoms. Her geno-identical younge sister was initially asymptomatic but then presented at the same age with severe EBV-driven infectious mononucleosis, which was treated aggressively and did not progress to HLH. The sisters had similar natural killer cell degranulation; however, while cytotoxic activity was moderately reduced in the asymptomatic patient, it was completely absent in both siblings during active disease. Following allogeneic bone marrow transplantation at the age of 15, the older child has completely recovered NK cell cytotoxicity, is asymptomatic and has experienced an exceptional compensatory growth spurt. Her younger sister was also successfully transplanted and is currently disease-free. The current study reveals previously unappreciated manifestations of FHL in patients who inherited hypomorphic gene variants, and also raises the important question of whether a threshold of minimum NK function can be defined that should protect a patient from serious disease manifestations such as HLH.